Percepção e o uso racional de energia elétrica: uma proposta pedagógica socioambiental - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
The relationship between man-nature-energy has guided the basis and development of science throughout its evolutionary trajectory. This research proposed to present a case study about the perception of students of the Federal Institute of Technological Education of Amazonas IFAM - Coari campus on the rational use of electricity, whose main objective was the construction of a teaching guide as a socio-environmental pedagogical tool. For this, the following categories of analysis were selected: environmental perception, teaching, and electric energy. The methodology is classified as exploratory, with a quali-quantitative approach, carried out remotely from April to June 2021, due to the restrictions imposed by the Covid-19 pandemic, relying on digital technologies and instruments in data collection. In the theoretical field, a cross methodology and a complex and interdisciplinary approach were chosen, with cross-cutting authors. The study pointed out that it is possible to sensitize students to the efficient, safe, and sustainable use of electricity through contextualized and interdisciplinary pedagogical practices. The final results pointed out that 65% of the participants reached indices of reduction in the consumption of electricity in their homes in comparison with the same period of the year before the research, 2020. The students experienced and learned in practice that electric energy conservation actions converge to positive socio-environmental impacts, reducing social and environmental costs, besides the re-signification of thinking in relation to the environment where they live, and, consequently, in relation to the world. The educational product (Didactic Guide - Pedagogical guidelines on the rational use of electric energy), built from the research, presents itself as a didactic-pedagogical support tool, especially for elementary school teachers, given the transversal character and the difficulties and challenges necessary for the inclusion and discussion of socio-environmental issues in school curricula. It can be adapted to any grade of Basic Education and widely disseminated in various educational institutions.
Keywords: Energia elétrica - Consumo; Energia - Consumo - Aspectos ambientais; Recursos energéticos - Conservação; Educação ambiental - Estudo e ensino; CIENCIAS HUMANAS: EDUCACAO; Percepção ambiental; Ciências ambientais; Ensino; Consumo de energia; Environmental perception; Environmental sciences; Teaching; Energy consumption